2015
DOI: 10.2147/dddt.s83588
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of trends of drug-prescribing patterns based on WHO prescribing indicators at outpatient departments of four hospitals in southern Ethiopia

Abstract: BackgroundRational prescribing is a primary step to ensure rational drug use. Often, half of the medicines are prescribed irrationally and half of these are even used incorrectly as the patients fail to take their medicines appropriately. The aim of this research was to evaluate drug-prescribing patterns of four hospitals in southern Ethiopia.MethodsA retrospective cross-sectional study was conducted between May 15 and June 25, 2014, to evaluate the drug-prescribing patterns based on the World health Organizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
4
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(67 citation statements)
references
References 8 publications
4
56
4
3
Order By: Relevance
“…This value is slightly lower than the ideal WHO standard (100%) [10]. In various outpatient settings around the globe, higher and closer to the standard values were reported such as 99.16% in GUTRH [19], 95.8% in four hospitals of southern Ethiopia [27], 98.7% in Hawassa University Teaching and Referral Hospital (HUTRH) [28], and 94.9% in Ayder referral hospital, Northern Ethiopia [29]. On the other hand, fewer values were documented in other health care settings including 83.1% in Pakistan [25] and 79.2% in southern Ethiopia.…”
Section: Discussionmentioning
confidence: 71%
“…This value is slightly lower than the ideal WHO standard (100%) [10]. In various outpatient settings around the globe, higher and closer to the standard values were reported such as 99.16% in GUTRH [19], 95.8% in four hospitals of southern Ethiopia [27], 98.7% in Hawassa University Teaching and Referral Hospital (HUTRH) [28], and 94.9% in Ayder referral hospital, Northern Ethiopia [29]. On the other hand, fewer values were documented in other health care settings including 83.1% in Pakistan [25] and 79.2% in southern Ethiopia.…”
Section: Discussionmentioning
confidence: 71%
“…A survey conducted in 8 hospitals in southern Ethiopia that investigated their prescription patterns concluded that irrational prescribing, as evidenced by high mean number of drugs prescribed per encounter, high percentage of injections, and high percentage of antibiotic use, was prevalent in the studied region [9]. A more recent study in four hospitals in the same region revealed that there was excessive use of antibiotics and injectable medications in the hospitals [10]. Another study that evaluated the WHO patient care indicators in South West Ethiopia also reported that there was a lower than the set values of patient knowledge on their medications, availability of essential guidelines and key drugs in stock in the health facilities [11].…”
Section: Introductionmentioning
confidence: 99%
“…Irrational drug prescribing usually leads to increased chances of treatment failure, antimicrobial resistance in case of antibiotics and social and economic burden on patient as well as on community as a whole. WHO and other standard guidelines always emphasize on the use of essential drugs with their generic names for the disease treatment 14,15 .…”
Section: Quick Response Codementioning
confidence: 99%